2018
DOI: 10.1002/ccd.27949
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 pharmacogenetics versus standard of care dosing for selecting antiplatelet therapy in patients with coronary artery disease: A meta‐analysis of randomized clinical trials

Abstract: Objectives This study aimed to evaluate the efficacy and safety of personalized genotype‐guided selection of antiplatelet therapy versus standard of care in patients undergoing percutaneous coronary intervention (PCI). Background Clopidogrel is the most frequently used P2Y12 receptor antagonist in patients with coronary artery disease. However, genetic variations of clopidogrel are associated with inter‐individual response variability which could limit its efficacy. Methods Electronic databases were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…17 The negative results of later meta-analyses can be explained by the heterogeneity of the population and inclusion in the meta-analyses of patients with a stable coronary disease. 18 Meanwhile, several large randomized clinical trials are in progress (Popular genetics (NCT01761786) -2700 patients; TAILOR-PCI (NCT01742117) -5270 patients) and the clinical application of genotype-based antiplatelet therapy remains controversial. Other P2Y12-inhibitorsticagrelor and prasugrel are not susceptible to the influence of allelic variants of the CYP2C19 gene carriership 19,20 and have appeared to be more potent in terms of decrease in thrombotic complications in comparison with clopidogrel among patients with acute coronary syndrome undergoing percutaneous coronary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…17 The negative results of later meta-analyses can be explained by the heterogeneity of the population and inclusion in the meta-analyses of patients with a stable coronary disease. 18 Meanwhile, several large randomized clinical trials are in progress (Popular genetics (NCT01761786) -2700 patients; TAILOR-PCI (NCT01742117) -5270 patients) and the clinical application of genotype-based antiplatelet therapy remains controversial. Other P2Y12-inhibitorsticagrelor and prasugrel are not susceptible to the influence of allelic variants of the CYP2C19 gene carriership 19,20 and have appeared to be more potent in terms of decrease in thrombotic complications in comparison with clopidogrel among patients with acute coronary syndrome undergoing percutaneous coronary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies of genetic testing have identified multiple genetic polymorphisms between individuals that could affect clopidogrel absorption, metabolism, and eventually its pharmacodynamic responses . Again, RCTs have failed to show their effectiveness in clinical practice . In our mixed treatment meta‐analysis, the results showed no significant differences between genotype‐ or phenotype‐guided antiplatelet therapy and the standard of care in patients undergoing coronary stenting.…”
Section: Discussionmentioning
confidence: 64%
“…Unfortunately, large randomized clinical trials (RCTs) that incorporated either platelet function assays or genetic testing have failed to demonstrate any clinical benefit . Furthermore, previous meta‐analyses of such strategies showed conflicting results . Therefore, we conducted a network meta‐analysis to evaluate the efficacy and safety of genotype‐ and phenotype‐guided intensified antiplatelet therapy compared with conventional therapy in patients undergoing stent implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a meta-analysis performed by Kheiri et al [46] was published, including six RCTs with a total of 2371 patients. Of those studies, only three trials included ACS patients [39,40,47], Tuteja et al [48] was not published and included CAD patients, Tomaniak et al [49] included stable CAD patients, and Robert et al [37] mainly included CAD (only 37% ACS).…”
Section: The Most Relevant Evidence In Pharmacogenetics Of Drugs Umentioning
confidence: 99%